The Flexing Phenomenon in Digital Society: An Islamic Economic Perspective on Consumption Ethics - Mutmainnah Mutmainnah; Ari Fahimatussyam; Abdur Rakhman Wijaya (Program Studi Ekonomi Islam Fakultas Ekonomi Universitas Nahdlatul UlamaNusa Tenggara Barat, 2023)
This study explores the growing phenomenon of flexing—the public display of wealth andluxury—within digital society from the perspective of Islamic economics. The research aims tounderstand how such self-presentations on social media reflect broader shifts in consumervalues, identity construction, and moral behavior. Employing a qualitative descriptive approachwith a library research method, this paper analyzes classical theories of conspicuousconsumption alongside Islamic teachings on moderation (wasathiyyah), humility, andresponsible ownership (amanah). The findings reveal that flexing culture represents atransformation of consumption from a functional activity into a symbolic performance thatseeks validation and social capital. From an Islamic economic perspective, this behaviorcontradicts the ethical principles of simplicity, gratitude, and social justice, potentially leadingto materialism and moral imbalance. The study concludes that strengthening spiritual literacy,ethical awareness, and the integration of Islamic consumption principles in digital spaces areessential to guide Muslims toward a more sustainable and equitable consumption pattern.